Pengaruh Media Balok Kayu terhadap Perkembangan Kreativitas Rancang Bangun pada Anak Usia 4-5 Tahun di TK Tunas Harapan ’82 Tenggilis Mejoyo Surabaya - Alfrianti Kusmarlaningsih; Aisyah, Aisyah (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Play is an important activity in a child's development and helps them in various aspects of their lives, such as motor, social, emotional, and cognitive. Playing wooden blocks is a type of educational game that can help children's development. This study aims to determine the influence of wood block media on the development of design creativity in children aged 4-5 years at Tunas Harapan Kindergarten '82 Tenggilis Mejoyo Surabaya. The research uses a quantitative method of quasi-experimental design, namely pretest-posttest control group design. The study sample consisted of 25 children divided into experimental and control groups with observation and documentation, analyzed using a paired sample t-test. Research shows that before being given treatment, most children are still in the less innovative category. After being treated using wood block media, there was a significant increase in children's design creativity. Statistical tests show that the significance value of < 0.001 means less than 0.05, meaning that there is a significant influence between the use of wood block media on children's creativity. Based on the results, it is recommended that educators use wooden block media regularly to increase children's creativity.